1995
DOI: 10.1079/bjn19950070
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exercise-induced maternal stress on fetal outcome in Wistar rats: Inter-generational effects

Abstract: The effects of physical activity during pregnancy and lactation on the fetal outcome and the growth of pups was studied in Wistar rats (n 144). Rats were trained to swim for 2 h every day, 6 d/week through pre-pregnancy, pregnancy and lactation. Maternal exercise during pregnancy, despite the dams having ad lib. access to food, resulted in low-birth-weight pups (5.6 (SD 0.7) g; n 178 in exercised dams v. 6.2 (SD 0.8) g; n 238 in sedentary dams). Maternal exercise continued through lactation exaggerated further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 15 publications
0
26
0
1
Order By: Relevance
“…Exercise during pregnancy leads to a reduced birth weight in the offspring and a hypotrophic intrauterine development (20). At P7, RUN pups were significantly lighter than CTR ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Exercise during pregnancy leads to a reduced birth weight in the offspring and a hypotrophic intrauterine development (20). At P7, RUN pups were significantly lighter than CTR ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the malnourished colony, the proportion of "small-forgestational-age" offspring was ten times higher than that for the well-nourished colony [93]. Similarly, Pinto et al recently reported the cumulative effects of exercise stress over successive generations [94].…”
Section: Effects Present In the F1 Persisting To The F2 And Beyondmentioning
confidence: 91%
“…Although most attention has been given to the 'first generation' of offspring exposed to a manipulation when in utero, there is a substantial body of evidence from animal studies that programmed phenomena can be perpetuated in later generations. Animal models of prenatal programming by nutrition or exercise, and postnatal programming by nutrition or handling have shown effects on birth weight (Stewart et al 1975, Pinto & Shetty 1995, glucose tolerance (Martin et al 2000, Patel et al 2001) and the hypothalamic-pituitary axis (Francis et al 1999) in subsequent generations.…”
Section: Intergenerational Effects In Animal Models Of Programmingmentioning
confidence: 99%